Neo-Ottoman memory of the „New Turkey" - Chudziak, Mateusz (Balcanica Posnaniensia. Acta et studia, 2024)
The article aims to present the process in creating of neo-Ottoman memory policy under the rule of the Justice and Development Party (AKP), which remains in power since 2002. In the first two decades of the 21st century, Turkey underwent a thorough transformation, including the replacement of elites, the undermining of the ideological foundations of the Kemalist republic, as well as the redefinition of Turkish nationalism and the state identity. The key element of these changes was the ongoing rehabilitation of the Ottoman Empire – relegated by the republic to the position of episode in the history of the Turks. As a result of creation of the the so-called "Turkish-Islamic synthesis" in the 1980s, as well as the development of social nostalgia for the former empire in the following decade, the new politics of memory, meeting this nostalgia, achieved spectacular success. However, it was conducted in a top-down manner, with great care taken to ensure that the content appearing in the public sphere was consistent with the intentions of the new power elite. This new memory, however, did not remove the republican heritage – its absorption became a key factor strengthening the legitimacy of “New Turkey” – monumental project of political and identity transformation.